An examination and critique of subjective methods to determine exercise intensity: the talk test, feeling scale, and rating of perceived exertion - Bok, D.; Rakovac, M.; Foster, C. (Sports Medicine, 2022)
Prescribing exercise intensity is crucial in achieving an adequate training stimulus. While numerous objective methods exist and are used in practical settings for exercise intensity prescription, they all require anchor measurements that are derived from a maximal or submaximal graded exercise test or a series of submaximal or supramaximal exercise bouts. Conversely, self-reported subjective methods such as the Talk Test (TT), Feeling Scale (FS) affect rating, and rating of perceived exertion (RPE) do not require exercise testing prior to commencement of the exercise training and therefore appear as more practical tools for exercise intensity prescription. This review is intended to provide basic information on reliability and construct validity of the TT, FS, and RPE measurements to delineate intensity domains. The TT and RPE appear to be valid measures of both the ventilatory threshold and the respiratory compensation threshold. Although not specifically examined, the FS showed tendency to demarcate ventilatory threshold, but its validity to demarcate the respiratory compensation threshold is limited. Equivocal stage of the TT, RPE of 10-11, and FS ratings between fairly good (+ 1) and good (+ 3) are reflective of the ventilatory threshold, while negative stage of the TT, RPE of 13-15, and FS ratings around neutral (0) are reflective of the respiratory compensation threshold. The TT and RPE can effectively be used to elicit homeostatic disturbances consistent with the moderate, heavy, and severe intensity domains, while physiological responses to constant FS ratings show extensive variability around ventilatory threshold to be considered effective in demarcating transition between moderate and heavy intensity domains.